The hydration of Li+ and Mg2+ in subnano carbon nanotubes using a multiscale theoretical approach - Liu, Ruirui; Jing, Zhuanfang; Shao, Yifan; Zhou, Yongquan; Zhu, Fayan; Liu, Hongyan (Frontiers in Chemistry, 2023)
The separation of brines with high Mg/Li mass ratios is a huge challenge. To provide a theoretical basis for the design of separation materials, the hydration of Li+ and Mg2+ in confinement using carbon nanotubes (CNTs) as the 1-D nanopore model was investigated using a multiscale theoretical approach. According to the analysis of the first coordination layer of cations, we determined that the coordination shells of two cations exist inside CNTs, while the second coordination shells of the cations are unstable. Moreover, the results of the structure analysis indicate that the hydration layer of Li+ is not complete in CNTs with diameters of 0.73, 0.87, and 1.00 nm. However, this does not occur in the 0.60 nm CNT, which is explained by the formation of contact ion pairs (CIP) between Li+ and Cl− that go through a unstable solvent-shared ion pair [Li(H2O)4]+, and this research was further extended by 400 ns in the 0.60 nm CNT to address the aforementioned results. However, the hydration layer of Mg2+ is complete and not sensitive to the diameter of CNTs using molecular dynamics simulation and an ab initio molecular dynamics (AIMD) method. Furthermore, the results of the orientation distribution of Li+ and Mg2+ indicate that the water molecules around Mg2+ are more ordered than water molecules around Li+ in the CNTs and are more analogous to the bulk solution. We conclude that it is energetically unfavorable to confine Li+ inside the 0.60-nm diameter CNT, while it is favorable for confining Li+ inside the other four CNTs and Mg2+ in all CNTs, which is driven by the strong electrostatic interaction between cations and Cl−. In addition, the interaction between cations and water molecules in the five CNTs was also analyzed from the non-covalent interaction (NCI) perspective by AIMD.